Effects of capillary pressure on multiphase flow during CO2 injection in saline aquifer - Pau, J.S. (EDP Sciences, 2014)
This paper focused on supercritical CO2 injection into saline aquifer, in particular its capillarity's effects on the plume migration, reservoir pressure alteration and CO2 flux density. The numerical method used to solve the incompressible two-phase flow equations is based on the mimetic method, which conserves the mass and fluxes simultaneously. The investigation showed that exclusion of capillarity can greatly underestimate the CO2 plume migration and resulted in distinctive reservoir pressure distribution. It is found that capillarity showed no significant effect on the flux intensity of CO2. Â© 2014 Owned by the authors, published by EDP Sciences.